Production of hydrogen from biomass and its separation using membrane technology. (February 2018) - Sołowski, Gaweł; Shalaby, Marwa.S.; Abdallah, Heba; Shaban, Ahmed.M.; Cenian, Adam
Abstract: Hydrogen is an important raw material for chemical industry and feasible renewable energy carrier that could replace fossil fuels. However, the specie seldom exists in a form of pure H2 . Therefore, to obtain hydrogen in volumes suitable to be used as a raw material it is necesary to decompose hydrogen-rich compounds. The carbohydrate-rich biomass can be an important source of hydrogen by applying the process of dark fermentation. In this paper potential ways of hydrogen production from organic wastes (biomass) by means of dark fermentation are reviewed and discussed. The bacteria used for dark fermentation are enlisted, characterized and compared. The pretreatment processes and various reactor designs are analyzed and discussed. The hydrogen separation by membrane method (which can provide the most pure hydrogen) are presented. The paper describes recent achievements in optimizing parameters, conditions and reactors used to industrialize dark fermentation.